Attitude to the childfree phenomenon of modern youth: regional aspect - V. V. Levchenko; Ya. O. Bayandina (Вестник университета, 2023)
The article provides an overview of key theoretical approaches to the phenomenon of voluntary and deliberate childlessness, or childfree phenomenon, which are used in modern sociological and socio-psychological science against the background of transformation of family values and the institution of family. The authors highlighted some of the patterns of the phenomenon specific to modern society and presented the results of an empirical study carried out with participation of Perm youth. These results allow to identify regional aspects of the attitude towards the childfree phenomenon by means of analyzing a set of parameters: the ideas that young people have of the childfree phenomenon; their emotional assessment of the phenomenon; awareness of the childfree social movement’s activities in the Russian Federation; attitude towards representatives of the social movement; willingness to support the ideas of the movement’s representatives; as well as willingness to have or not to have children. The authors also analyzed the main factors that influence the formation of young people’s attitude towards the childfree phenomenon and the corresponding social movement.